Subnational Credit Rating: A Comparative Review - LIU, Lili (Institutional Knowledge at Singapore Management University, 2009)
This paper surveys methodological issues in subnational credit ratings and highlights key challenges for developing countries. Subnational borrowing from capital markets has been on the rise owing to fiscal decentralization and demand for infrastructure investments. A prerequisite for accessing capital markets, subnational credit ratings have also emerged as a part of broader reform for fiscal sustainability. They facilitate a more transparent budgetary and financial management system. The global financial crisis makes subnational credit ratings more relevant, as they contribute to fiscal risk evaluations and fiscal adjustment. In addition to subnationals’ own credit strength, the creditworthiness of the sovereign and the intergovernmental fiscal system are among the most critical rating criteria. Implicit and contingent liabilities are integral to the rating process. Indirect debt instruments including off-balance-sheet financing create fiscal risks. The ongoing financial crisis has reinforced the rating focus on the management of liquidity, debt structure, and off-balance-sheet liabilities.